2021
DOI: 10.1080/2090598x.2021.1889746
|View full text |Cite
|
Sign up to set email alerts
|

The impact of varicocelectomy on sperm DNA fragmentation and pregnancy rate in subfertile men with normal semen parameters: A pilot study

Abstract: Objective: To evaluate the outcome of microscopic subinguinal varicocelectomy on sperm DNA fragmentation (SDF) and pregnancy rate in men with normal semen parameters. Patients and methods: A pilot study that included male patients with a minimum of a 1-year history of male subfertility, normal semen parameters, a high percentage of SDF, and clinically palpable varicoceles. Microscopic subinguinal varicocelectomy was carried out for 45 patients (study group), while 40 patients had no intervention (control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…It should be highlighted that some factors can be eliminated, while diagnostic parameters can be modified using proper medical management based on examination and in-depth medical interviews. Recent studies have shown that modification of unhealthy habits (e.g., smoking, alcohol abuse, drugs, and being overweight), administration of antioxidant therapy, and varicocelectomy in cases of varicocele-mediated infertility can contribute to restoring physiological levels of ROS and to improving semen quality, including the integrity of sperm DNA [ 8 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 21 , 29 , 48 ]. Moreover, in the era of growing numbers of chronic disease cases (e.g., insulin resistance, cancers, cardiovascular disease, and being overweight), it cannot be ignored that the adoption of healthy habits can additionally improve general male health and may contribute to a lower cost of medical care in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be highlighted that some factors can be eliminated, while diagnostic parameters can be modified using proper medical management based on examination and in-depth medical interviews. Recent studies have shown that modification of unhealthy habits (e.g., smoking, alcohol abuse, drugs, and being overweight), administration of antioxidant therapy, and varicocelectomy in cases of varicocele-mediated infertility can contribute to restoring physiological levels of ROS and to improving semen quality, including the integrity of sperm DNA [ 8 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 21 , 29 , 48 ]. Moreover, in the era of growing numbers of chronic disease cases (e.g., insulin resistance, cancers, cardiovascular disease, and being overweight), it cannot be ignored that the adoption of healthy habits can additionally improve general male health and may contribute to a lower cost of medical care in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, approximately 15% of adult men have varicoceles, but in the population of infertile men, the prevalence rises to 40% (primary infertility) or even to 80% (secondary infertility) [ 4 , 5 , 6 , 7 , 8 ]. Therefore, proper medical examination of the scrotum is essential for the management of male infertility [ 4 , 5 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…After varicocoelectomy, low DNA fragmentation index is associated with a higher pregnancy rate. 12,13 Reduced oxidative stress post antioxidant treatment and varicocoele repair has been associated with improved pregnancy rates in infertile men with varicocoele. 14,15 The present evidences support that varicocoele affects spermatogenesis via several distinct mechanisms such as scrotal hyperthermia, hypoxia, backflow of toxic metabolites, elevated oxidative stress, hormonal deregulation and testicular hypo-perfusion (Figure 1) 2 ; however, the definite cause of varicocoele-associated infertility still remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced SDF after varicocoelectomy improves the chance of spontaneous pregnancy in these individuals. After varicocoelectomy, low DNA fragmentation index is associated with a higher pregnancy rate 12,13 . Reduced oxidative stress post antioxidant treatment and varicocoele repair has been associated with improved pregnancy rates in infertile men with varicocoele 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…Few controlled studies have assessed the difference in pregnancy outcomes after varicocelectomy for infertile men with elevated sperm DNA fragmentation. In a recent study by Fathi et al (5) assessing the impact of varicocelectomy in infertile men with clinical varicocele and elevated sperm DNA fragmentation, the investigators found a 62% pregnancy rate in 45 men undergoing surgical varicocele correction compared with a 30% pregnancy rate in 40 men who did not undergo varicocelectomy. While these findings certainly are encouraging, important questions remain.…”
mentioning
confidence: 99%